Genetic diversity of maize (Zea mays L.) Jala race using ISSR molecular markers - Suárez-González, G.; López-Guzmán, G.; León-Fernández, A.; Bautista-Rosales, P. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2025)
Maize (Zea mays L.) is the crop of greatest national and global importance, both due to the area planted and the volume of production and its diversity of uses. Mexico stands out for having the greatest diversity of maize in the world, being the origin of its domestication. In the state of Nayarit, 16 races have been reported, highlighting the Jala race as one of the most important maize races in Mexico; due to its unique morphological characteristics such as ear length, plant height and late life cycle. Currently, diversity analysis is carried out through molecular markers. The characterization of this diversity helps the improvement, conservation and protection of plant races. In this study, eight ISSR-type molecular markers were used with the objective of characterizing the genetic diversity present in representative samples of Jala maize from different sites and samples of hybrid maize. The eight markers detected between seven and ten bands in all samples, whose molecular weights ranged between 200 and 2000 bp. An average of 202 alleles were found per marker. The average expected heterozygosity (He) value was 0.205. 95.66% of the bands were polymorphic, with respect to the number of effective alleles (Ne), the average obtained in the study was 1,343, while the number of different alleles (Na) obtained on average was 1,347. The highest percentages of polymorphisms, He, Ne and Na were found at the “El Llano” site. The Molecular Analysis of Variance AMOVA showed higher percentages (62%) in the variation within populations than between populations. Cluster analysis determined three groups. Group I, included 11 genotypes from the El Llano and Jala la Vieja sites; Group II included 22 genotypes belonging mostly to Jala la Vieja and Tiltón; Group III, included 22 genotypes mainly from Tepic and Jomulco. The results suggest that although there is genetic richness in the Jala breed, its genetic variability has been reduced.